Selective deficit of visual size perception: two cases of hemimicropsia. Issue 1 (January 1994) - Cohen, L; Gray, F; Meyrignac, C; Dehaene, S; Degos, J D
Abstract : Hemimicropsia is a rare disorder of visual perception characterized by an apparent reduction of the size of objects when presented in one hemifield. We report two cases of hemimicropsia resulting from focal brain lesions. The first patient was an art teacher and could accurately depict his abnormal visual perception. He subsequently died and his brain was examined post mortem. In the second patient, micropsia was assessed by a quantified size comparison task. The size of a given object is normally perceived as constant across any spatial position. Hemimicropsia may thus be considered a limited violation of the size constancy principle. Behavioural and anatomical data are discussed in relation to the neural basis of visual object perception in humans.